Teacher Education in Light of a Few Principles, Theories, and Studies on Vocational Training and Adult Education - Mayen, Patrick (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2011)
The objective of this article is to critically examine teacher education based on the concepts, principles, and practices of adult education, vocational training, and continuing vocational training. We will discuss a few aspects of teacher education from the perspective of our research and our theoretical frames of reference, touching on the fields of initial and continuing vocational training, as well as adult education, work psychology, and developmental psychology (Pastré, Mayen, & Vergnaud, 2006, Mayen, 2007). We will also draw from a research study on professional work and training in very different sectors: railroad transportation, public works, agriculture, human services, technical-commercial services, guidance, and orientation. This allows us to examine teaching in the light of what we know of other forms of work, and teacher education in the light of what we know of vocational training and adult education.